History of horizontal anchor plates based on experimental works in cohesion less soil - Niroumand, H. (2011)
Buried anchors have been used for thousands years to stabilize structures. Anchor plates may be made of steel plates, precast concrete slabs, poured concrete slabs, timber sheets and so forth. This paper presents the history of anchor plates in experimental works in cohesion less soils due to different researches by last researchers from first research until now. The role of this last experimental research has focused on predicting anchor behavior and force in cohesion less soil. Although there are not entirely sufficient substitutes for full-scale field testing, tests at laboratory scale have the advantage of allowing close control of at least some of the parameters encountered in research. These anchors can be installed by excavating the ground to the required depth and then backfilling and compacting with good quality cohesion less soils. The results are involved of laboratory testing that they are typically problem specific and they are difficult to extend to field problems with different material or geometric parameters in field scale. The paper observed that the ultimate uplift capacity is dependent on the relative friction angle, density based on loose or dense conditions and the depth ratio of embedment.